Comparison and testing the reliability of two non-radiographic techniques of mixed dentition space analysis in Nepalese population - Mishra, Rajeev Kumar; Devagiri, Vashant (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Mesio-distal tooth size-arch length discrepancy is one of the major sources of malocclusion. Accurate prediction of space required for unerupted tooth can help in early interception of developing malocclusion. Various methods has been proposed for prediction of mesio-distal tooth size however accuracy of such methods in population groups other than that on which these methods are based remains questionable. The aims and objectives of this study were to test the reliability of Moyer’s and Tanaka Johnston mixed dentition analysis in Nepalese population, to construct prediction tables for Nepalese population if these methods were found not reliable. Materials & Methods: Study models of 77 subjects (31 males,46 females) fulfilling the inclusion criteria were retrieved from department archive. Tooth dimensions were measured using electronic digital caliper. Moyer’s and Tanaka and Jhonston methods were applied to predict the mesio- distal tooth size of canines and premolars. The predicted values were compared with the actual mesio-distal mesio-distal size. A regression equation based on actual canine and premolar mesio-distal dimensions and sum of mandibular permanent incisors was also developed. Results: Independent t-test showed that there was no significant difference between mesio-distal tooth size in males and females. Paired t-test showed that there was no difference in mesio-distal tooth size between right and left sides of the arch. Tanaka – Johnston analysis overestimated the mesio-distal size in both males and females. Moyer’s method at 75% overestimated the mesio-distal size in male and female and the difference were statistically significant while at 50% it underestimated the tooth size in females. Conclusion: Moyer’s and Tanaka and Jhonston method of mesio-distal size prediction are inaccurate when applied in Nepalese population. A new regression equation to predict the size of tooth has been presented.